Dose- and application route-dependent effects of betahistine on behavioral recovery and neuroplasticity after acute unilateral labyrinthectomy in rats - Antons, Melissa; Lindner, Magdalena; Eilles, Eva; Günther, Lisa; Delker, Astrid; Branner, Christina; Krämer, Anja; Beck, Roswitha; Oos, Rosel; Wuehr, Max; Ziegler, Sibylle; Strupp, Michael; et al. (Frontiers in Neurology, 2023)
Introduction Betahistine is widely used for the treatment of various vestibular disorders. However, the approved oral administration route and maximum daily dose are evidently not effective in clinical trials, possibly due to a major first-pass metabolism by monoamine oxidases (MAOs). The current study aimed to test different application routes (i.v./s.c./p.o.), doses, and concurrent medication (with the MAO-B inhibitor selegiline) for their effects on behavioral recovery and cerebral target engagement following unilateral labyrinthectomy (UL) in rats. Methods Sixty rats were subjected to UL by transtympanic injection of bupivacaine/arsanilic acid and assigned to five treatment groups: i.v. low-dose betahistine (1 mg/kg bid), i.v. high-dose betahistine (10 mg/kg bid), p.o. betahistine (1 mg/kg bid)/selegiline (1 mg/kg once daily), s.c. betahistine (continuous release of 4.8 mg/day), and i.v. normal saline bid (sham treatment; days 1–3 post-UL), respectively. Behavioral testing of postural asymmetry, nystagmus, and mobility in an open field was performed seven times until day 30 post-UL and paralleled by sequential cerebral [18F]-FDG-μPET measurements. Results The therapeutic effects of betahistine after UL differed in extent and time course and were dependent on the dose, application route, and selegiline co-medication: Postural asymmetry was significantly reduced on 2–3 days post-UL by i.v. high-dose and s.c. betahistine only. No changes were observed in the intensity of nystagmus across groups. When compared to sham treatment, movement distance in the open field increased up to 5-fold from 2 to 30 days post-UL in the s.c., i.v. high-dose, and p.o. betahistine/selegiline groups. [18F]-FDG-μPET showed a dose-dependent rCGM increase in the ipsilesional vestibular nucleus until day 3 post-UL for i.v. high- vs. low-dose betahistine and sham treatment, as well as for p.o. betahistine/selegiline and s.c. betahistine vs. sham treatment. From 1 to 30 days post-UL, rCGM increased in the thalamus bilaterally for i.v. high-dose betahistine, s.c. betahistine, and p.o. betahistine/selegiline vs. saline treatment. Discussion Betahistine has the potential to augment the recovery of dynamic deficits after UL if the administration protocol is optimized toward higher effective plasma levels. This may be achieved by higher doses, inhibition of MAO-based metabolism, or a parenteral route. In vivo imaging suggests a drug-target engagement in central vestibular networks.